Vulnerability factors among women victimized by intimate partner violence and the presence of children - Petersson, Joakim (Journal of family violence, 2022)
This study aimed to a) examine the presence of children in relation to victim vulnerability factors and assessed risk for intimate partner violence (IPV) re-victimization, and b) examine the police response, in terms of risk management, in IPV cases with and without children, respectively. Data from a sample of 1407 women who had reported IPV victimization to the Swedish police was analyzed. The material consisted of risk assessments conducted by the police using the Swedish version of the Brief Spousal Assault Form for the Evaluation of Risk (B-SAFER) checklist, as well as the recommended risk management strategies. A series of chi-square tests of independence revealed that women with and without children, respectively, displayed different vulnerability factors to different extents. Women with children expressed more extreme fear of the perpetrator and were more likely to have an unsafe living situation, whereas women without children displayed more inconsistent attitudes or behaviors and health problems. However, binary logistic regression analyses showed that the victim vulnerability factors that were most strongly associated with an elevated risk rating for IPV re-victimization were generally the same for both groups of victims. Finally, the presence of children was related to a higher risk rating for imminent IPV re-victimization and to recommendations of more than standard levels of risk management strategies. The results indicate that the Swedish police consider the presence of children in relation to a victim’s risk for re-victimization as well as in terms of recommended risk management strategies.